A study on energy use (Electricity) in residential buildings / Mohamad Hilman Azwan Zainal Abidin - Zainal Abidin, Mohamad Hilman Azwan (Faculty of Architecture, Planning and Surveying, 2010)
Electricity is the energy that has been used daily for lighting, heating or cooling. Residential building use energy to doing normal activities like using the computer, watching television, cooking and so on to perform their work. All of this activities consuming a lots of electricity energy and includes the technical basis for defining human comfort. Electricity is a delivered energy produce from either the primary energy or secondary energy. However, the price of oil and cost of producing electrical energy was highly increased. As electricity user we are responsible to take part to save on our electricity bill. This study has three (3) main objectives which are, to identify energy used (electricity) in Low cost and medium cost terrace and flat house, to identify factors that influence electricity energy usage in residential buildings through occupancies, space and environmental condition and to suggest the suitable mechanism for electricity energy saving in residential building. From the finding and analysis it can identify the factors that influence the use of electricity in residential buildings such as passive design factor, building occupancies and the use of electrical equipment per day. For the conclusion and recommendation it shows the ways how to makes the building more comfortable for the occupant such as the use of green roof system and plant surrounding the house with green element will helps to decreased electricity bills every months.